Field-induced tricritical phenomenon and magnetic structures in magnetic Weyl semimetal candidate NdAlGe. (4th January 2022) - Zhao, Jun; Liu, Wei; Rahman, Azizur; Meng, Fanying; Ling, Langsheng; Xi, Chuanying; Tong, Wei; Bai, Yuming; Tian, Zhaoming; Zhong, Yunbo; Hu, Ying; Pi, Li; et al.
Abstract: Non-centrosymmetric NdAlGe is considered to be a candidate for magnetic Weyl semimetal in which the Weyl nodes can be moved by magnetization. Clarification of the magnetic structures and couplings in this system is thus crucial to understand its magnetic topological properties. In this work, we conduct a systematical study of magnetic properties and critical behaviors of single-crystal NdAlGe. Angle-dependent magnetization exhibits strong magnetic anisotropy along the c -axis and absolute isotropy in the ab -plane. The study of critical behavior with H ∥ c gives critical exponents β = 0.236(2), γ = 0.920(1), and δ = 4.966(1) at critical temperature T C = 5.2(2) K. Under the framework of the universality principle, M ( T, H ) curves are scaled into universality curves using these critical exponents, demonstrating reliability and self-consistency of the obtained exponents. The critical exponents of NdAlGe are close to the theoretical prediction of a tricritical mean-field model, indicating a field-induced tricritical behavior. Based on the scaling analysis, a H – T phase diagram for NdAlGe with H ∥ c is constructed, revealing a ground state with an up-up-down spin configuration. The phase diagram unveils multiple phases including up-up-down domains, up-up-down ordering state, polarized ferromagnetic (PFM), and paramagnetic (PM) phases, with a tricritical point (TCP) located at the intersection [ T TCP = 5.27(1) K, H TCP = 30.1(3) kOe] of up-up-down, PFM, and PM phases. The multiple phases and magnetic structures imply a delicate competition and balance between variable interactions and couplings, laying a solid foundation for unveiling topological properties and critical phenomena in this system.